(untitled) (Analysis in Theory and Applications, 2025)
In this paper, the parabolic Schrödinger operator P=_t-+V(x) on R^n+1 is considered, where n3, nonnegative potential V belongs to the reverse Hölder class RH_q with q n /2. The L^p boundedness of operators V^αP^-β, V^α ablaP^-β and their adjoint operators are established.